Identification of the chemical profile and evaluation of the antimicrobial effect of Eryngium billardieri Delar essential oil component against bacterial species of agricultural and food interest - Hajian-Maleki, Habibeh; Shams-bakhsh, Masoud (Frontiers in Microbiology, 2023)
Studies on the antibacterial activity of the essential oil of E. billardieri are limited. In this study, we identified this herb as a natural complex effective against several bacteria by employing disk diffusion and broth microdilution susceptibility methods. Primary estimation of the antimicrobial effect of this herbal compound by disk diffusion method showed that the oil could inhibit the growth of the tested bacteria by the appearance of haloes between 8.25 and 21.25 mm. In the next step, the oil was found to be active against all 24 tested Gram-negative and Gram-positive bacteria in the broth media, at minimum inhibitory concentrations ranging from 0.67 to 34.17 g L−1. Furthermore, Enterococcus faecalis and Curtobacterium flaccumfaciens pv. flaccumfaciens were the most sensitive food and plant pathogenic bacteria, respectively. Gas chromatography–mass spectrometry analysis was conducted to assign the ingredients present in the oil; 34 different components representing 95.71% of the total oil were identified, with n-hexadecanoic acid being the dominant component, followed by 2-Pentadecanone, 6,10,14-trimethyl, 1H-Indene, 1-ethylideneoctahydro-, and Cinnamyl tiglate. These findings demonstrate, for the first time, a broad spectrum of the antibacterial capacity of E. billardieri. Based on these observations, the oil could be applied as a natural preservative with the potential for designing novel products. Its bioactive agents can also be isolated for further use in the food and agricultural industries.